MicroRNA 200a inhibits erythroid differentiation by targeting PDCD4 and THRB. (13th October 2016) - Li, Yanming; Zhang, Qian; Du, Zhenglin; Lu, ZhiChao; Liu, Shuge; Zhang, Lu; Ding, Nan; Bao, Binghao; Yang, Yadong; Xiong, Qian; Wang, Hai; Zhang, Zhaojun; et al.
Summary: Previous studies on erythropoiesis revealed that microRNAs (miRNAs) play a critical role in erythroid differentiation. Given the abundance of identified miRNAs and the limited understanding of erythroid miRNAs, additional examination is required. Here, two sets of erythroid differentiation miRNome data were analysed to screen for novel erythroid‐inhibiting miRNAs. MIR200A was selected based on its pattern of downregulated expression in the miRNome datasets during induction of erythroid differentiation. Overexpression of MIR200A in K562 and TF‐1 cells confirmed its inhibitory role in erythroid differentiation. Further in vivo study indicated that overexpression of mir200a inhibited primitive erythropoiesis of zebrafish. Transcriptome analyses after MIR200A overexpression in TF‐1 cells indicated a significant role in regulating erythroid function and revealed potential regulation networks. Additionally, bioinformatics and experimental analyses confirmed that PDCD4 (programmed cell death 4) and THRB (thyroid hormone receptor, beta) are both targets of MIR200A ‐3p. Gain‐ and loss‐of‐function studies of PDCD4 and THRB revealed that the two targets were capable of promoting erythroid gene expression. Overall, our results revealed that microRNA 200a inhibits erythroid differentiation by targeting PDCD4 and THRB .